Cohesion as a bonding tool in translation of English into Northern Sotho : an interaction between translation and discourse analysis - Kgatla, Mohale Edward (My University, 2012)
Refer to the document
Thesis (M.A. (Translation Studies and Linguistics )) -- University of Limpopo, 2012
Keywords: Cohesion; Northerbn Sotho language; Cohesion (linguistics); Discourse analysis -- South Africa; Translating and interpreting -- South Africa